The cardiometabolic profile and related dietary intake of Ugandans living with HIV and AIDS - Kiyimba, Tonny; Kigozi, Fred; Yiga, Peter; Mukasa, Barbara; Ogwok, Patrick; Van der Schueren, Bart; Matthys, Christophe (Frontiers in Nutrition, 2022)
Introduction Suboptimal diet and physical inactivity downgrade the putative benefits of Antiretroviral Therapy (ART) among People Living with HIV (PLWH). However, there is paucity of literature on dietary intake and cardiometabolic profiles of PLWH in Uganda. Methods A cross-sectional study among PLWH in Uganda was conducted. Dietary intake was assessed using a 24h recall method of 2 non-consecutive days. The short International Physical Activity Questionnaire assessed participants' physical activity. Fasted blood samples were analyzed for Fasting Blood Glucose (FBG), total cholesterol, LDL-c, HDL-c and triglycerides. Blood pressure and anthropometric measurements were performed following step 2 of the WHO STEPS. Results 253 patients completed in this study. A high prevalence of low HDL-c (31.9%), abdominal obesity (44.5%), high BMI (51.6%), raised FBG (45.3%), high SBP (31.5%), elevated triglycerides (26.4%) and metabolic syndrome (28%) was found. More women were identified with metabolic syndrome (31.5%) than men (19.2%). Low prevalence of high LDL-c (4.7%) and total cholesterol (9.8%) was found. Diets had a high carbohydrate (65.8 ± 10.4) E% and fiber intake (30.1 ± 12.7) g with minimal PUFA (6.1 ± 2.3) E%, fruits and vegetables (1.4 servings). High proportions were found of unmet intake for vitamin A (38.2%), B1(48.8%), B2 (29.6%), B12 (29%), folate (61.4%), Ca (76%), Zn (53.1%) and Mg (41.7%). Mean MET min was 6,700 ± 5,509 and over 68% of the participants had >3,000 MET min. Conclusion Our findings reveal a high prevalence of metabolic disturbances among PLWH in Uganda and further highlight that their diets are suboptimal with low fruits and vegetable intake